Analysis of the Influence of Leadership Style and Work Motivation on Employee Performance (Literature Review) - Sirait, Radja Martin; Isnanto, Samto Hadi (Dinasti Publisher, 2025)
The success rate of employee performance can be determined by the leadership within a company, specifically by examining the leadership style implemented. Leadership style is an approach or method chosen to direct and influence subordinates so that the company's productivity level, effectiveness, profitability, performance, and employee motivation can be achieved in accordance with the desired goals. An effective leadership style in managing company resources will naturally influence employee behavior, as indicated by the creation of work motivation, which in turn will ultimately affect the company's overall performance. The literature review provides a framework related to new findings and previous findings in identifying indications of progress or lack thereof in the results of a particular study. The method used in the literature review follows a systematic approach to analyzing data through a simplified approach. The stages involved in the simplified approach analysis include summarizing each piece of literature, conducting a critical appraisal simultaneously to determine the strengths and weaknesses of the literature, and examining the relationship between one piece of literature and another. The author considers all research designs used in identifying the influence of leadership style and work motivation on employee performance.